PELAKSANAAN KEWENANGAN ATRIBUSI PEMERINTAHAN DAERAH BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - HSB, ALI MARWAN; JULIANTHY, EVLYN MARTHA (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2018)
In the practice of the implementation of regional autonomy in Indonesia, the Regional Government has the authority to regulate its own territory by the division of authority as regulated in Act No. 23 of 2014 on Local Government. These powers are matters related to concurrent matters comprising compulsory and optional matters. The question is in the form of a legal product whether local governance regulates these authorities. Based on the search of various provisions of the legislation it can be concluded that the regulation on the exercise of the authority of attribution is to be by local regulations. This is directly related to the content of regional regulatory content, one of which is in the context of regional autonomy. In this regard, it is suggested that in relation to the exercise of the authority of attribution or concurrent affairs of local government shall be governed by regional regulations.